Pengaruh Strategi Pembelajaran dan Self Efficacy Terhadap Hasil Belajar menulis - La Ode Nggawu (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2020)
This study aims to determine the effect of learning strategies (Word Wall Strategy and Dirrect Instruction Strategy) and the student self efficacy toward writing learning outcomes of english study programme Halu Oleo University. This research uses experimental design with a 2x2 treatment by level with sample number of 54 students at English education study programon academic year 2019/2020. The data analysis was done by Analysis of Variance (ANAVA) two lane. The results showed that (1) Word Wall Strategy (WWS) was more effective in improving writing learning outcomes than Dirrect Learning Strategy (DL); (2) there was a significance interaction effect between learning strategies and student's self efficacy toward writing learning outcomes 3) students’ writing learning outcomes who uses Word Wall Strategy are higer than direct instruction strategy with students higher self efficacy, (4) and for students with low self efficacy more appropriate using dirrect Learning strategies (DL).